Electronic resources in academic libraries and its contribution towards sustainable development goals / Wan Nor Haliza Wan Mokhtar ... [et al.] - Wan Mokhtar, Wan Nor Haliza; Shaifuddin, Norshila; Mohamad, Adi Azri; Ahmmad Rofee, Fatin Hanisah; Rambeli, Shahidatul Akhmam; Mohd Nasir, Mohd Alfarabie (Faculty of Information Management, 2023)
Electronic Resources which also known as the online resources play very important role in academic libraries each day. During the Pandemic Covid19 especially, the use of electronic resources in academic libraries became increasingly higher. As part of technological developments provided by academic libraries, it is important to note the roles of electronic resources in contributing toward the SDGs. Academic libraries must observe electronic resources as critical components of the information delivery chain because they help to upsurge access to existing knowledge in appropriate curricula and resources for the learning of fundamental skills, including reading, numeracy, and life skills. This paper attempts to critically examine the previous literature, with the objective of identifying the main themes of research on the electronic resources in academic libraries and the contributions towards the United Nation's initiatives which is better known as the Sustainable Development Goals (SDGs). A total of 60 articles were undertaken using searches of Scopus and Web of Science (WoS) databases, were included in this review, covering three major research themes, consist of - electronic resources, academic libraries as well as Sustainable Development Goals (SDGs). Theories and framework related to electronic resources from previous research provide public libraries with a guide to the factors that may affect the Sustainable Development Goals initiatives in the academic libraries.